Advances in aptamer-based biosensors and cell-internalizing SELEX technology for diagnostic and therapeutic application - Gan, Zixuen; Mohamad Roslan, Muhamad Aidilfitri; Abd Shukor, Mohd Yunus; Halim, Murni; Yasid, Nur Adeela; Abdullah, Jaafar; Md Yasin, Ina Salwany; Wasoh, Helmi (Multidisciplinary Digital Publishing Institute, 2022)
Aptamers are a group of synthetic single-stranded nucleic acids. They are generated from a random library of single-stranded DNA or RNA by a technology named systematic evolution of ligands by exponential enrichment (SELEX). SELEX is a repetitive process to select and identify suitable aptamers that show high affinity and specificity towards target cells. Great strides have been achieved in the design, construction, and use of aptamers up to this point. However, only a small number of aptamer-based applications have achieved widespread commercial and clinical acceptance. Additionally, finding more effective ways to acquire aptamers with high affinity remains a challenge. Therefore, it is crucial to thoroughly examine the existing dearth and advancement in aptamer-related technologies. This review focuses on aptamers that are generated by SELEX to detect pathogenic microorganisms and mammalian cells, as well as in cell-internalizing SELEX for diagnostic and therapeutic purposes. The development of novel aptamer-based biosensors using optical and electrical methods for microbial detection is reported. The applications and limitations of aptamers are also discussed.